Characterisation polymorphims of genotype microsatellite in association with body weight of Aceh cattle - Sari EM; Yunus N; Jianlin H; Muchti . (Indonesian Center for Animal Research and Development (ICARD), 2013)
The objectives of this research was to evaluate polymorphism of microsatellite DNA through the investigation of loci BM1824, SPS115, and ILSTS028, and their possible association with body weight of Aceh cattle. A total of 121 of DNA samples were collected from Aceh cattle population in Indrapuri. Genetic polymorphism of Aceh cattle was calculated in frequency of alleles and genotypes. Association between genotypes and body weight was calculated by general linear model (GLM). Result showed that three loci showed high polymorphism. BM1824 locus had 11 genotypes with 3 highest frequency for BC (30.87), CC (17.28) then BB (14,82), while frequency of the other 8 genotypes namely : AB, AC, AD, AF, BD, BE, BF, and CD were less than 10 %. SPS115 locus had 9 genotypes with two highest frequency for CE (30.00) and BE (20.00), while the other 7 genotype were less than 15%. ILSTS028 locus had 22 genotypes with two highest frequencies for CH (24.69) and CC (13.59) respectively. It is conduded that Aceh cattle possessing typical genotypes of BE in BM1824 locus, AE in SPS115, and BG in ILSTS028 locus was apparently related to a higher body weight compared to other genotypes. On the contrary, those possessing AB in BM1824 and CK genotypes in ILSTS028 were seemingly associated with a lower body weight. Key Words: Aceh Cattle, Microsatellite, Body Weight